RELATIONSHIP BETWEEN SURFACE HYDROPHOBICiTY, HAEMAGGLUTTNATION AND ADHERENCE MECHANISM OF STREPTOCOCCUS SUIS - Siti Isrina Oktavia Salasia (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 1995)
Streptococcus suis is well known as the causative agent of disease in various animal including pigs and human. The streptococcal cultures isolated from pigs and human have been characterized and identified biochemically and serologically as Streptococcus suis. The Cultures could be serotyped with 28 different monospecific antisera. Tne result of tins study indicated that the predominant antigen types of the S. suis cultures belonged to serotypes 2, 1/2, 1. The occurrence of the type specific microcapsule appeared to be realed with the surface hydrophobicity of the bacteria. Toe surface hydrophobicity could be demonstrated by hexadecan adherence tests. The S. suis cultures with hydrophobic surface agglutinated erythrocytes of humans, pigs and rabbits. The relationship between surface hydrophobicity, haemagglutinating and adherence properties of cultures could be demonstrated with 3 cell models. The haemagglutinating cultures adhered in high number to HeLa cells, ephitelial cells and to alveolar macrophages from rabbits. The non haemagglutinating cultures with hydrophobic surfaces adhered only to ephitelial cells and to alveolar macrophages S, suis cultures with hydrophilic surfaces showed no comparable reaction with 3 cell models.